“We were all together”- families’ experiences of the health-promoting programme – A Healthy Generation - Susanne Andermo; Matthias Lidin; Mai-Lis Hellenius; Anja Nordenfelt; Gisela Nyberg (BMC Public Health, 2020)
Abstract Background Healthy lifestyle habits, including physical activity (PA), are associated with a broad range of positive psychosocial and physical health benefits. However, there are challenges involved in reaching vulnerable groups in socioeconomically disadvantaged areas. There is a lack of research on family-based PA interventions, specifically considering psychosocial health. The purpose of this study was to explore how families experienced psychosocial aspects of health after participation in a family-based programme, A Healthy Generation. Methods A Healthy Generation is a health-promoting, family-based programme delivered in collaboration with local municipalities and sport associations in socioeconomically disadvantaged areas in Sweden. Families with children in grade 2 (8–9 years), including siblings, participate in health-promoting activities, including activity sessions, healthy meals, health information and parental support groups. Data was collected through interviews with parents and children (n = 23) from a controlled pilot trial of the programme. Interviews were audio recorded, transcribed and analysed using a phenomenological hermeneutical method. Results Three themes and seven sub-themes emerged. The themes were: “A sense of belonging”, “Awareness of one’s role as a parent” and “Inspiration towards new and healthier behaviours”. In terms of A sense of belonging, participation in the programme was the families own free zone, where they also had the opportunity of being together with other families in the programme. For participants that were isolated and lacked a social network, their participation helped them towards social participation. During the programme, parents created an Awareness of one’s role as a parent, with new insights on how to act as a parent and they also negotiated differences between each other. Participation in the programme contributed to Inspiration towards new and healthier behaviours such as experience-based insights and healthy lifestyle changes. Conclusions This study highlights the importance of co-participation in family-based health-promoting programmes to enhance psychosocial health among families in socioeconomically disadvantaged areas. The results give new insights into participants’ experiences of psychosocial aspects of health after participation in a family-based PA programme. This knowledge can contribute to the understanding of how to design health-promoting, family-based interventions to promote psychosocial health in socioeconomically disadvantaged areas. Trial registration ISRCTN ISRCTN11660938 . Retrospectively registered 23 September 2019.